DYNAMIC CRUSHING OF HONEYCOMBS WITH A NEGATIVE POISSON’S RATIO—A FINITE ELEMENT STUDY - LU ZiXing; LI Kang (Jixie qiangdu)
The deformation modes and energy absorption properties of honeycombs with a negative Poisson’s ratio under inplane dynamic crushing were studied by means of finite element simulation in this paper. The results show that behavior mechanism of negative Poisson’s ratio under dynamic crushing is the same with that at static loading of which is the cave-in or rotation,and this explains the necking phenomena of the stagger-arranged triangle and quadratic cells during the in-plane crushing. The results provide us a certain understanding of the dynamic behavior and energy absorption property of twodimensional cellular materials with a negative Poisson’s ratio and lay the foundation of the impact behavior of three-dimensional foam materials with a negative Poisson’s ratio.